Photovoltaic smart grids in the prosumers investment decisions: A real option model - Marta Castellini; Francesco Menoncin; Michele Moretto; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2019)
The digitization of power system represents one of the main instruments to achieve the target set by the European Union 2030 climate and energy Agenda of affordable energy transition. During the last years, such innovation process has been associated with the Smart Grid (SG) term. In this context, efficiency and flexibility of power systems are expected to increase and energy consumers to be active also on the production side, thus becoming prosumers (agents that both produce and consume energy). This paper provides a theoretical real option framework with the aim to model prosumers' decision to invest in photovoltaic power plants, assuming that they are integrated in a Smart Grid. Our main focus is to study the optimal plant size and the optimal investment threshold, in a context where exchange of energy among prosumers is possible. The model was calibrated and tested with data from the Northern Italy energy market. Our findings show that the possibility of selling energy between prosumers, via the Smart Grid, increases investment values. This opportunity encourages prosumers to invest in a larger plant compared with the case without exchange possibility and that there is a positive relation between optimal size and (optimal) investment timing. The effect of uncertainty is in line with the literature, showing increasing value to defer with volatility.
Keywords: Q42; C61; D81; 330; Smart Grids; Renewable Energy Sources; Real Options; Prosumer; Peer to Peer Energy Trading